(untitled) (Journal of the College of Education for Women, 2019)
As we know the transportation studies regarded as one of a veryimportant and difficult studies and one of its difficulties created from theprocess of data updating therefore the researcher well facing many difficultiesto balancing between the old data on collecting new data.The research present an opinion which is summarized by: can we usethe old data after we updated and used it as alternatives? Or the researchermust collect new data to complete their research which indicate to the presentsituation and some times they cant complete their studies because of thesecurity, economic, temporally difficulties.The research used two kinds of data, the old data which belong to theperiod (1998) and new data which belong to the period (2008) and applied onthe deterrence function of work trips.The main conclution of the research is that the old data are moresignificance than the new data and therefor we can use it as alternative insuch studies.